The Performance Appraisal Interview – An Arena for the Reinforcement of Norms for Employeeship - Sandlund, Erica; Olin-Scheller, Christina; Nyroos, Lina; Jakobsen, Liselotte; Nahnfeldt, Cecilia (Nordic Journal of Working Life Studies, 2011)
In the present paper, we report findings from a study of performance appraisal interviews between middle managers and employees. The study is based on analysis of video uptake of authentic performance appraisal interviews, and through detailed examination of participant conduct and orientation, we point to structural mechanisms and institutional norms which limit the possibilities for employees to raise topics connected to negative experiences of stress in performance ap- praisal talk. It is argued that norms concerning ideal employeeship are shaped by a partly hidden curriculum in the organization which in turn is talked into being in the performance appraisal interviews.The study concludes that empirical attention to the social interplay in performance ap- praisal interactions reveal how participant conduct aligns or disaligns with institutional and social underpinnings of workplace ideals.